Co-simulation of CFD-multiphase population balance coupled model aeration of sludge flocs in stirrer tank bioreactor. (February 2020) - Wodołażski, Artur
Highlights: Performance multiphase population balance full-transient CFD models for multiphysics modelling in different time scales is coupling by co-simulation as a novel technique. Influence of the CFD hydrodynamics on population balance multiphase interaction on the microbiological kinetic growth and thus the increase of biomass was determined. A coupled CFD-PBE-biokinetics-Simplorer approach was used. Effect of temperature, aeration flow rate, floc size and impeller rotation speed on biomass growth was studied. Abstract: Aerated stirrer tank bioreactors are commonly used to convert organics and remove nutrients through microbial floc environments. Computational Fluid Dynamic CFD based on multiphase approach coupled with gas (air) and solid (sludge flocs) population balance models (pbm) are using in co-simulation to modelling dynamics complex multiphysics phenomena in different time scales. Co-simulation coupled CFD-PBM-kinetic models to captured the biomass growth kinetics and the influence of the reactor hydrodynamics on the overall process. Floc size distribution is crucial as it determines distinct grades of final floc structures, which are to be used as commercial aerobic wastewater treatment respectively. The coupled population balance equation was solved using an inhomogeneous discrete method of the continuous partial differential equation for sludge flocs and standard methods of moments for gas phase, which were then solved simultaneously and influence on biomass kinetics growth. Additionally, the influence of the agitator's speed and air flow rate on dynamic biomass growth have been investigated in full transient CFD analysis. The kinetics of biomass growth rate, as a function of oxygen saturation and air/flocs population balance was employed in the model through User Defined Function (UDF). The integrated modelling multiphysics in a multiphase system methodology by co-simulation represents a valuable tool to examine the impact of individual parameters of the biomass growth in the bioreactor. Graphical abstract: Image, graphical abstract